Nuances do masculino em José Lins do Rego: a trajetória do personagem Ricardo - Cavalcante, Raíssa Vale Miranda (2020)
The discussion about masculinities in Brazilian literature is relatively recent in the field of cultural studies. In regional literature, it is possible to find the literary representation of an arid like the land male, the "cabra-da-peste". However, there is in José Lins do Rego's works a protagonist, the character Ricardo, who has in himself transient nuances of the masculine, sometimes closer to what is socially agreed upon as pertinent to the female gender and other times closer to what is agreed upon socially as the male gender. The present paper seeks to investigate the masculine gender identity in the novels “O Moleque Ricardo” (1935) and “Usina” (1936) by José Lins do Rego. The research is divided into three chapters. The first one is a historical overview of the social construction of masculinity from the contributions, mainly, of Oliveira (2004), Connell (2013) and Badinter (1993). In the second chapter, the focus will be on the contribution of the spatial category as a complementary topoanalytical methodology for the construction of the character Ricardo, taking Albuquerque Júnior (2013), Bakhtin (2018) and eBachelard (1993) as references. Finally, in the third chapter, there's an examination of the relationships between some characters in the narratives, especially among those with whom Ricardo became emotionally involved. For this, the analyzes of Elizabeth Badinter (1993), Pierre Bourdieu (2002) and Nolasco (1993) were discussed.